PENGARUH KEMAMPUAN DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA PEGAWAI YANG DIMEDIASI DENGAN MOTIVASI KERJA PEGAWAI DINAS PERHUBUNGAN KOTA BANJARMASIN - Riky Welli Saputra; Cici Asmawatiy; Misransyah Akos (Administraus, 2018)
This research entitled "The Influence Of Ability And Work Environment To Employee Work Performance That Are Focused With Job Motivation Of Banjarmasin City Transportation Officer" which aims to know the description of ability, environment, motivation and job performance and to test the influence of ability and work environment to the work performance of employees mediated by employee motivation. This study uses quantitative research samples are applied as many as 48 respondents. Data collection using questionnaires and documentation. While data analysis using path analysis assisted with software SmartPLS 30. The results of this study indicate that the ability and environmental variables are simultaneously able to explain the motivation variable of 46.7%, the remaining 55.3% is explained by other variables that are not hypothesized in the model. The next result for the variable ability, environment, and motivation able to explain the work performance variable of 46.3%, the remaining 53.7% explained by other variables that are not hypothesized in the model.